Wykorzystanie ukrytych modeli Markowa do klasyfikacji spółek giełdowych - Kasprzyk, Iwona (Application of Latent Markov Model to Companies Stock Classification, 2007)
The main purpose of this paper is to show the latent Markow models, which we can use to financial analysis. This article shows the earning per share ratio analysis as one of the most important ratios for the potential investment on stock exchange. This kind of models has been proposed by Wiggins [1973] and they are combining of the latent class models and simple Markov model. These models can be used to describe individual change in categorical variables.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 115-121